Mechanical analysis of a portal steel frame when subjected to a post-earthquake fire - Merouani, Mohammed Redha (2020)
Fire or earthquake pose a significant threat to the human life, and cause an enormous damage to the structures, moreover the dual effect of a Post-Earthquake Fire (PEF) is a major hassle to designers and rescuers alike. Designers, when considering Algerian seismic rule (RPA99v2003) [1], ignore the possibility of a post-earthquake fire, whose effect can lead to the dramatic collapse of the structures.